The Implementation of Reading Listen-Read-Discuss (LRD) Strategy in Teaching Reading Comprehension - Puspitaloka, Nina; Nur Kholifah, Khofifatul; Zakiyatunnisa, Salsabila (Universitas Cokroaminoto Palopo, 2025)
Reading comprehension is a crucial skill in English learning, yet many Indonesian EFL students still face difficulties in understanding texts. This study aimed to investigate the implementation of the Listen-Read-Discuss (LRD) strategy in teaching reading comprehension and to explore students’ perspectives on its effectiveness. The research employed a qualitative descriptive design with junior high school students as participants. Data were collected through classroom observation and semi-structured interviews and analyzed thematically. The findings revealed that the teacher implemented the three stages of LRD consistently and systematically. The listening stage provided a model of fluent reading that helped students capture the main ideas, the reading stage offered opportunities for independent practice and vocabulary reinforcement, and the discussion stage promoted interaction, interpretation, and collaborative meaning-making. From the students’ perspective, LRD made reading lessons more motivating, enjoyable, and supportive of comprehension. However, several challenges emerged, particularly limited vocabulary knowledge and unequal participation during discussions, which suggest that adaptation is needed to optimize its use. Overall, this study confirms that LRD is an effective strategy for teaching reading comprehension in EFL contexts while also extending previous research by highlighting contextual obstacles in Indonesian classrooms. The results imply that teachers may integrate vocabulary pre-teaching, visual aids, and structured discussion techniques to enhance the effectiveness of LRD. Future research is recommended to test this strategy with larger samples, different text types, and digital-based adaptations to broaden its pedagogical contribution.